Non syndromic unilateral dentigerous cyst in a 4-year-old child: A rare case report - T N Tilakraj; N K Kiran; K S Mukunda; Shwetha Rao (Wolters Kluwer Medknow Publications, 2011)
Dentigerous cyst is the most prevalent type of odontogenic cyst and is associated with crown of an unerupted or a developing tooth and accounts more than 24% of jaw cysts. Here, we present an interesting case of dentigerous cyst in a 4-year-old boy, which developed around an unerupted maxillary first premolar. Histological examination revealed a cyst with 1-2-cell-thick epithelial lining and presence of inflammatory cells in the connective tissue.